2007
DOI: 10.1111/j.1600-6143.2007.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Oxidation Provoked by Nitric Oxide Radicals Predicts the Progression of Acute Cardiac Allograft Rejection

Abstract: Bilirubin, a strong intrinsic antioxidant, quenches free radicals produced under inflammatory conditions. The oxidized bilirubin metabolites, i.e. biopyrrins, are immediately excreted into urine and can indicate the intensity of oxidation in vivo. Our preliminary studies suggested the involvement of reactive nitrogen species (RNS) in generation of biopyrrins. However, little is known about biological significance of bilirubin oxidation by RNS. Here, we analyzed the correlation between bilirubin oxidation and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
1
14
2
Order By: Relevance
“…30,31 Biopyrrins are immediately excreted in urine because of their hydrophilic properties and thus can reflect the severity of oxidative stress. 25,[32][33][34][35][36][37][38] Biopyrrin synthesis reflects NO radicals, 25 so urinary biopyrrin levels can indicate ongoing changes in oxidative stress in vivo and thus function as a marker of oxidative stress.The time course of urinary and tissue biopyrrin levels in rat models of cardiac transplantation and hepatic ischemia reperfusion has been investigated. 25,32 A cardiac transplantation study showed that levels of urinary biopyrrins become more rapidly and sensitively elevated than either urinary 8-hydroxy-2'-deoxyguanosine or serum troponin-T during …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…30,31 Biopyrrins are immediately excreted in urine because of their hydrophilic properties and thus can reflect the severity of oxidative stress. 25,[32][33][34][35][36][37][38] Biopyrrin synthesis reflects NO radicals, 25 so urinary biopyrrin levels can indicate ongoing changes in oxidative stress in vivo and thus function as a marker of oxidative stress.The time course of urinary and tissue biopyrrin levels in rat models of cardiac transplantation and hepatic ischemia reperfusion has been investigated. 25,32 A cardiac transplantation study showed that levels of urinary biopyrrins become more rapidly and sensitively elevated than either urinary 8-hydroxy-2'-deoxyguanosine or serum troponin-T during …”
mentioning
confidence: 99%
“…30,31 Biopyrrins are immediately excreted in urine because of their hydrophilic properties and thus can reflect the severity of oxidative stress. 25,[32][33][34][35][36][37][38] Biopyrrin synthesis reflects NO radicals, 25 so urinary biopyrrin levels can indicate ongoing changes in oxidative stress in vivo and thus function as a marker of oxidative stress.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of recipients with these agents either prolonged graft survival [35,36], had no effect on graft survival [37,38] or decreased graft survival [39]. None of these studies provided information on either graft function prior to graft failure or independent evaluation of histological rejection scores.…”
Section: Evidence Using Broad-spectrum Nos Inhibitorsmentioning
confidence: 99%